The Effect of Chewing Sugar-Free Gum to Improve Bowel Movement After Colorectal Surgeries in Patients With Colorectal Cancer - Mohammad Al-kharabsheh MSc; Huda Alwahedi RN; Jaber Elhamshary RN; Lina Younis MSc; Mahmoud Al Masri MB (SAGE Open Nursing, 2023)
Introduction Colorectal cancer is classified as the second most prevalent type of cancer among males and females in Jordan; approximately 1260 (10.9%) out of 11559 cases were diagnosed with colorectal cancer in 2020. According to American statistics, colorectal cancer is the third leading cause of cancer-related deaths among both males and females, as well as the second leading cause when combining both numbers . Objective The current study aimed to assess the effectiveness of chewing gum in reducing postoperative ileus in patients with cancer after colorectal surgeries and evaluate the length of hospital stay (LOS) after colorectal resection, complications, and costs. Methods One-hundred twenty-nine patients who underwent colorectal surgeries at a specialized cancer center in Jordan from April 2019 to May 2020 were recruited. After colorectal surgeries, patients were randomized into two groups. The control group (69 patients) received conventional postoperative care; the experimental group (60 patients) was asked to chew free sugar gum over one hour in the morning, noon, and evening until the first flatus. Result The passage of the first flatus was significantly shorter in the experimental group (mean 48.02 h) than in the control group (116.45); p  = .001. Also, there was a significant difference between both groups according to gender and age. Conclusion Chewing free sugar gum after colorectal surgeries can significantly improve the recovery of bowel motion by accelerating the time to first auscultation to bowel sounds, the first passage of flatus, and reduction in the LOS, which went in agreement with many studies. However, chewing gum is considered a safe, cheap, and practical method to reduce ileus.